Relationship CHANGE: How to Change Your Relationships for GOOD - Victor William Harris (EDIS)
“Everything would be fine if my partner would just change!” This is a common sentiment many of us have felt. However, this notion is just the opposite of how we should go about changing our relationships for good. Positive change is never easy. This 3-page fact sheet introduces the principle of Change Yourself First as a healthy strategy for changing our relationships. Written by Victor William Harris, and published by the UF Department of Family, Youth and Community Sciences, March 2012.